Inter and intra maxillary elastic have impact on orthodontic management - a systematic review and meta-analysis - Alam , Mohammad Khursheed; Abutayyem , Huda; Shayeb , Maher AL; Ibrahim , Maysara Adnan (Bangladesh Journal of Medical Science, 2025)
Objectives: The study aimed to compare the effects of intermaxillary elastics (IMEs) and intramaxillary elastics (IAEs) in orthodontic treatment and provide evidence-based recommendations for their usage. Eligibility criteria: Articles that examined the effects of IMEs and IAEs in orthodontic treatment were considered. A total of 10 papers, 5 for each type of elastic, were included in the final analysis. Information sources: PubMed, Embase, Cochrane Library and Scopus were searched to identify relevant articles. Risk of bias: Cochrane’s risk of bias tool was utilised for the assessment of the risk of bias. Included studies: Ten papers were included in the study, with 5 each focused on IMEs and IAEs. Both types of elastics were found to be associated with significant improvements in orthodontic management. The OR for noticeable vs negligible impact was 0.44 for IMEs and 0.48 for IAEs, indicating a significant association. Synthesis of results: A meta-analysis was conducted, and forest plots were generated to assess the odds ratio (OR) for IMEs and IAEs separately. The analysis showed a positive correlation between the use of both types of elastics and orthodontic management. One study indicated that appliance therapy was slightly more effective than IAEs. The forest plot for IMEs showed no significant heterogeneity, while the plot for IAEs showed moderate heterogeneity. The findings suggest that both IMEs and IAEs are viable options for orthodontic management, although some heterogeneity was observed in the studies regarding IAEs. Limitations of evidence: The review was limited to studies published in the English language, which could have led to the exclusion of relevant studies published in other languages. Also, the review only included studies published from 2013 onwards, which could have resulted in the exclusion of relevant older studies. Interpretation: The study’s results support the use of both IMEs and IAEs in orthodontic treatment, indicating their positive effects. Further research may be needed to address the observed heterogeneity in studies focusing on IAEs. Registration and protocol: The research protocol was developed and registered with PROSPERO [CRD42023405593]. The study adhered to the PRISMA guidelines for the search and inclusion of relevant articles. BJMS, Vol. 24 No. 03 July’25 Page : 995-1006